2010
DOI: 10.1111/j.1398-9995.2009.02221.x
|View full text |Cite
|
Sign up to set email alerts
|

Multicentre trial evaluating alveolar NO fraction as a marker of asthma control and severity

Abstract: Alveolar and exhaled NO fractions are not indexes of control or severity in asthmatic children and adults under treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
48
1
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 32 publications
10
48
1
5
Order By: Relevance
“…In this study, J’awNO showed a trend toward increased values in patients with more severe asthma than those with milder disease. However, when CANO(TMAD) was determined using a trumpet model with axial diffusion that estimated NO concentrations exiting the respiratory bronchioles and alveolar region, CANO(TMAD) was not correlated with disease severity, which is consistent with a recent finding by Mahut et al [26]. Given that CANO is not adjusted for NO axial diffusion from conducting airways and could be more contaminated by small-airway NO diffusion than CANO(TMAD), this discrepancy between previous findings with CANO and those with CANO(TMAD) in this study may indicate that small-airway inflammation influences asthma severity to a greater extent than the actual alveolar inflammation.…”
Section: Discussionsupporting
confidence: 81%
“…In this study, J’awNO showed a trend toward increased values in patients with more severe asthma than those with milder disease. However, when CANO(TMAD) was determined using a trumpet model with axial diffusion that estimated NO concentrations exiting the respiratory bronchioles and alveolar region, CANO(TMAD) was not correlated with disease severity, which is consistent with a recent finding by Mahut et al [26]. Given that CANO is not adjusted for NO axial diffusion from conducting airways and could be more contaminated by small-airway NO diffusion than CANO(TMAD), this discrepancy between previous findings with CANO and those with CANO(TMAD) in this study may indicate that small-airway inflammation influences asthma severity to a greater extent than the actual alveolar inflammation.…”
Section: Discussionsupporting
confidence: 81%
“…The lack of correlation between FENO and asthma control has been previously reported both in adults and children [20][21][22]. A weak correlation between asthma control, evaluated with ACT, and FENO was described by Japanese authors in a cohort of 105 patients with a high prevalence of uncontrolled asthma (60%) [23].…”
Section: Discussionmentioning
confidence: 88%
“…38 Two studies demonstrated no association between alveolar NO values and ACQ scores. 28,29 The studies of Oosterhoff et al 42 ACT, Asthma Control Test; BDI, Baseline Dyspnea Index; CC, closing capacity; CT, computed tomography; CV, closing volume; dN2, slope of phase III of SBNT; FOT, forced oscillation technique; FRC, functional residual capacity; FVC, forced vital capacity; IC, inspiratory capacity; R5, resistance of the respiratory system at 5 Hz; R20, resistance of the respiratory system at 20 Hz; R5-R20, difference of R5 and R20; Rp, peripheral lung resistance; SF6, sulfur hexafluoride; VC, vital capacity; X5, reactance of the respiratory system at 5 Hz.…”
Section: Discussionmentioning
confidence: 97%